Adult Education and Lifelong Learning in Europe and Beyond Comparative Perspectives from the 2015 Wuerzburg Winter School - Egetenmeyer, Regina (Studien zur Paedagogik, Andragogik und Gerontagogik / Studies in Pedagogy, Andragogy, and Gerontagogy, 2016)
This volume presents comparisons of adult education and lifelong learning with a focus on educational policies, professionalization in adult education, participation in adult learning and education, quality in adult education, and educational guidance and counselling. The essays are based on comparisons discussed at the international Winter School «Comparative Studies in Adult and Lifelong Learning», held in Würzburg, Germany, February 2015. Sub-topics of lifelong learning were chosen for an in-depth comparison and analysis of the situation in various European countries and beyond.